Cross-sectional study on the seroprevalence, reinfection, and associated factors of Chlamydia trachomatis among female sex workers in Guangdong Province, China - Peizhen Zhao; Lei Xu; Yinna Huang; He Huang; Junhe Chen; Weiming Tang; Lijun Mo; Qingqing Xu; Shujie Huang; Cheng Wang; Heping Zheng; Bin Yang; et al. (BMC Infectious Diseases)
Abstract Background Female sex workers (FSWs) are at high risk of chlamydia infection, yet the seroprevalence among FSWs in China remains unclear. This study aimed to determine the seroprevalence of Chlamydia trachomatis and associated factors among FSWs in Guangdong Province, China. Methods A cross-sectional study was conducted among FSWs in two cities in Guangdong Province. Participants provided serum and urine samples. Nucleic acid amplification test (NAAT) was used to detect Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) in urine samples. Enzyme-linked immunosorbent assay (ELISA) was used to detect chlamydia IgG antibodies in serum samples. Seropositivity was defined by IgG-positive results. Current chlamydia infection was identified by a positive NAAT result, while prior infection was indicated by positive chlamydia IgG and negative NAAT results. Reinfection was defined by positive results for both NAAT and chlamydia IgG. Moreover, positive ELISA results were reclassified into two categories: DU/mL values ≥ 37.89 (the median) were classified as high-positive and DU/mL values > 11 to 37.89 as low-positive. Sociodemographic data, CT and NG testing, and paper questionnaires were collected through face-to-face interviews. Univariate and multivariable logistic regressions explored factors associated with current CT infection. Results A total of 435 serum and urine samples were analyzed. The median age of the participants was 32.0 (IQR: 27.0–37.0) years. Among the participants, 326 were CT IgG positive, resulting in an overall seroprevalence of 74.9% (95% CI, 70.6–78.9). The current infection proportion determined by NAAT was 12.2% (53/435) (95% CI, 9.3–15.6), significantly lower than the IgG seroprevalence. Seroprevalence was higher among those over 39 years (88.6%) compared to those under 20 years (62.5%). High seroprevalence was observed among NAAT-negative participants (74.3%, 95% CI, 69.7–78.7). Single, divorced, or widowed individuals had higher seroprevalence (78.4%, 95% CI, 72.9–83.1) compared to married ones (69.5%, 95% CI, 61.9–76.3) (P < 0.05). Among seropositive participants, 42 were both NAAT and chlamydia IgG positive, indicating a reinfection proportion of 12.9% (95% CI, 9.4–17.0). Among reinfections, 81.0% had high seropositivity and 19.0% had low seropositivity. Reinfection prevalence was highest in those under 20 years (50%, 95% CI, 18.7–81.3) (P < 0.05). Conclusion This study found a high prevalence of anti-chlamydia IgG among FSWs, including those who were NAAT-negative. Additionally, there was a high reinfection proportion among Chinese FSWs. CT serological assays are increasingly recognized as valuable epidemiological tools. Younger FSWs and those new to transactional sex may be at higher risk and should be prioritized for community-based prevention interventions to reduce the burden of CT transmission. Overall, CT serological assays are increasingly recognized as valuable tools for epidemiological surveillance and intervention. Clinical trial number Not applicable.